Dinâmica do carbono e nitrogênio dissolvidos na região do Baixo Rio Amazonas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
The Amazon River play an important role in transporting and processing of nutrients towards the ocean. However, there is a gap in the understanding of this river as a link between the terrestrial and marine environment, due to few studies in this region, tidally influenced. Here, we document the spatial-seasonal variability of dissolved carbon and nitrogen concentrations and fluxes from Óbidos to the mouth of the Amazon River, in addition to assessing the influence of this region on the regional budget, of C and N dissolves forms, during the period of 2014 and 2017. DOC, DIC and TDN concentrations were determined by infrared absorption, on the equipment Shimadzu, model TOC-VCPH, generated after combustion at 690°. DIN was result of the sum of nitrite, nitrate and ammonium fractions, which were determined by automated flow injection system calorimetry. DON concentrations were obtained by the difference between the TDN fraction and the DIN fractions. DOC and DON concentrations in the Amazon river mainstem and its clearwater tributaries are mainly influenced by the input of allochthonous material, during rising and high water. During the period of high water and falling water, there was a dilution of the DOC concentrations between Óbidos and Almeirim. Likewise, dilutions occurred in the concentrations of DIC and DON, however, only in the period of low water. In this stretch, dilutions were associated with the entry of clear water tributaries and a higher rate of degradation of organic matter, due to the contribution of substrates of algal origin, causing negative mass balances. Near the mouth, dilutions in DOC concentrations and increases in DIC concentrations were observed in the period of low water, events also associated with the occurrence of priming effect, however, possibly related to low molecular weight substrates and sugars. With regard to dissolved nitrogen, there was an increase in NID concentrations near the mouth, possibly associated with higher O2 saturation. The average export of dissolved carbon and nitrogen was 59 Tg C yr-1 and 2 Tg N yr-1, respectively, with significant influence from the lower Amazon on the regional budget, mainly regarding the export of dissolved nitrogen.
Keywords: Fluxos; Carbono; Nitrogênio; Efeitos de Maré; Balanço de Massa; CNPQ::CIÊNCIAS BIOLÓGICAS